Top 10 research priorities to improve the everyday life of older patients with multimorbidity: A James Lind Alliance (JLA) inspired Priority Setting Partnership (PSP) - Karoline Madsen; Torunn Wibe; Asta Bye; Jonas Debesay; Astrid Bergland (Tidsskrift for Omsorgsforskning)
Introduction: A central tenet of national health and social care policy is to ensure that services support people in achieving their personal well-being and health outcomes, including people with multimorbidity. In Norway, research is needed that addresses multimorbidity in old age in community health services. Aim: The aim of this publication is to report results from a JLA inspired approach to identify a top 10 list of potential priorities within the scope of coordination and continuity of health services for home-dwelling older adults with multimorbidity. Methods: Through a JLA-inspired PSP, the method was conducted through 5 stages: (1) setting up a steering group, (2) establishing a PSP, (3) developing potential research questions, (4) processing, categorising and summarising these research questions, (5) determining top 10 priorities. Results: The 131 respondents identified 486 uncertainties. The top priorities were related to communication between community health professionals and how information can reach frail older adults. Conclusion: Researchers looking for relevant research questions will be able to address these top 10 questions provided by clinicians and older adults in the context of community health care.